CK1α overexpression correlates with poor survival in colorectal cancer - Richter, Julia (BMC Cancer, 2018)
BACKGROUND: Colorectal cancer (CRC) is the fourth leading cause of cancer related deaths worldwide and prognosis in advanced tumor stage still remains poor. Since CK1 isoforms have been reported to be deregulated in several tumor entities CK1 has emerged as a novel drug target in cancer therapy. In this study we set out to investigate whether CK1α might have the potential to serve as prognostic marker. METHODS: CK1α RNA and protein expression levels in healthy and tumor tissue of CRC patients were analyzed using quantitative real-time PCR and Western Blot analysis, respectively. Prognostic relevance was investigated by correlating obtained CK1α expression levels with patients’ survival rate generating Kaplan-Meier survival plots. RESULTS: It could be shown that CK1α is overexpressed in colorectal tumor tissue compared to normal tissue and CK1α overexpression in tumor tissue correlates with poor survival in CRC patients. Results become more significant when only considering patients with high-grade tumors, as well as patients assigned to UICC II and UICC III stage. Furthermore, Cox regression analysis revealed that CK1α is an independent prognostic factor. In addition, tumors expressing decreased levels of the kinase reveal positive effects on overall survival when localized in the right colon compared to those in the left side. CONCLUSION: In summary, this study provides evidence for the first time that CK1α RNA levels might serve as prognostic marker for CRC. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-018-4019-0) contains supplementary material, which is available to authorized users.